AN EVALUATION OF SAPI BALI BREEDING ASSISTANCE PROGRAM IN SAWERIGADI DISTRICT, WEST MUNA REGENCY - Banardin; La Ode Asrad Sani; Amiluddin Indi (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2026)
Bali cattle are a genetic resource native to Indonesia, raised by local communities because they are relatively easy to care for and offer certain advantages over other beef cattle, including the ability to adapt to low-quality feed and a relatively high fertility rate. The recipients of the Bali cattle assistance program in Sawerigadi Subdistrict are small-scale farmers and livestock breeders with limited economic resources. In addition to serving as a program to increase the population and income of the rural community, the Bali cattle assistance provided in Sawerigadi Subdistrict also reflects important social dynamics that warrant evaluation. This study aims to analyze the outcomes and impacts of the government’s program regarding the provision of Bali cattle assistance in Sawerigadi Subdistrict, West Muna Regency. The methods employed in this study include observation, interviews, and documentation, analyzed using descriptive analysis. The respondents in this study were selected through a census, comprising all recipients of Bali cattle assistance from 5 villages, totaling 333 individuals. The results of this study indicate that: (1) The Bali cattle procurement assistance program in Sawerigadi Subdistrict, West Muna Regency, has successfully increased the population from the initial 333 calves distributed between 2018 and 2023 to 609 head, comprising 283 males and 326 females. (2) The government program has had a positive impact on beneficiary communities in terms of: (a) funding education and healthcare; (b) meeting clothing and food needs; (c) home renovations; (d) funding transportation; and (e) an increasing livestock population.